Photocatalytic activity of tetracycline hydrochloride in mariculture wastewater degraded by CuO/Bi2O3 under visible light. Issue 17 (22nd November 2021) - Zhu, Wanting; Yu, Xiaocai; Liao, Jiaqi; Fu, Jiayuan; Li, Zejun; Zhang, Yong Xia
ABSTRACT: CuO/Bi2 O3 photocatalysts were successfully prepared by coprecipitation. The morphology of CuO was like seedlings, growing on the surface of Bi2 O3 and forming nanoparticles with enhanced surface properties. Compared with pure Bi2 O3, CuO/Bi2 O3 nanocomposites showed a higher catalytic reaction interface and photocatalytic efficiency toward target pollutants. Six single-factor experiments were designed to investigate the performance advantages of the as-designed nanoparticles. These characteristics showed that the as-obtained CuO/Bi2 O3 composite(s) could have enlarged applicability. The optimum conditions for the degradation of tetracycline hydrochloride by composite photocatalyst were obtained by six factors and five levels orthogonal experiment. The optimal conditions for the degradation of tetracycline hydrochloride pollution in mariculture wastewater by composite photocatalyst CuO/Bi2 O3 were the calcination temperature of 350°C, the calcination time of 2 h, the dosage of 1.4 g/L, the concentration of H2 O2 of 0.4 g/L, the initial concentration of antibiotics of 0.01 g/L, and the illumination time of 3 h. The decrease rate of solution under optimized conditions was 99.72%. After four cycles of repeated experiments, the degradation rate of photocatalyst can still reach more than 90%. It is proved that the repetitive stability of synthetic materials. These characteristics make CuO/Bi2 O3 have practical application value.